2023
DOI: 10.1146/annurev-biophys-101122-071930
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Dynamics of Intrinsically Disordered Proteins from Single-Molecule Spectroscopy

Abstract: Many proteins contain large structurally disordered regions or are entirely disordered under physiological conditions. The functions of these intrinsically disordered proteins (IDPs) often involve interactions with other biomolecules. An important emerging effort has thus been to identify the molecular mechanisms of IDP interactions and how they differ from the textbook notions of biomolecular binding for folded proteins. In this review, we summarize how the versatile tool kit of single-molecule fluorescence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 184 publications
(282 reference statements)
2
14
0
Order By: Relevance
“…As both preparations contain intact NPCs, and indeed (i) the oocyte preparation with its intact NE has been shown to be structurally intact (Eibauer et al, 2015) and fully transport-competent (Siebrasse and Peters, 2002) and (ii) the isolated yeast NPCs have been shown to be competent for rapid nuclear transport factor exchange (Hakhverdyan et al, 2021), these results strongly support the in vivo relevance of our observations. IDPs show characteristic long-range conformational chain dynamics that span timescales of between 100 ns and 1 ms (Chowdhury et al, 2023). Effectively the dynamic "fuzzy" motion of the FG domains is downsampled in HS-AFM measurements, which we tested by simulating the HS-AFM experiment using a Brownian dynamics computational model of the NPC; this also confirmed that the HS-AFM sampling rate yielded information relevant to the pertinent time scales (Fig.…”
Section: Fg Domains Fluctuate Radially Towards the Central Plugsupporting
confidence: 56%
“…As both preparations contain intact NPCs, and indeed (i) the oocyte preparation with its intact NE has been shown to be structurally intact (Eibauer et al, 2015) and fully transport-competent (Siebrasse and Peters, 2002) and (ii) the isolated yeast NPCs have been shown to be competent for rapid nuclear transport factor exchange (Hakhverdyan et al, 2021), these results strongly support the in vivo relevance of our observations. IDPs show characteristic long-range conformational chain dynamics that span timescales of between 100 ns and 1 ms (Chowdhury et al, 2023). Effectively the dynamic "fuzzy" motion of the FG domains is downsampled in HS-AFM measurements, which we tested by simulating the HS-AFM experiment using a Brownian dynamics computational model of the NPC; this also confirmed that the HS-AFM sampling rate yielded information relevant to the pertinent time scales (Fig.…”
Section: Fg Domains Fluctuate Radially Towards the Central Plugsupporting
confidence: 56%
“…While the phrase coupled binding and folding is quite frequently used while discussing protein functionality, it is important to keep in mind that even "folding" is best described as a part of continuum, in which the disorder of the protein is retained in the complex in a wide range with "fuzzy complexes" as one extreme end of the spectrum (Chowdhury et al, 2023;Freiberger et al, 2021;Fuxreiter, 2012Fuxreiter, , 2018Fuxreiter, , 2019Fuxreiter, , 2020Fuxreiter & Tompa, 2012;Gruet et al, 2016;Miskei et al, 2020Miskei et al, , 2017Sharma et al, 2015Sharma et al, , 2019Tompa & Fuxreiter, 2008;Welch, 2012). A recent review by Chowdhury et al comprehensively covers the insights on protein-protein interactions (involving IDPs/IDRs) from the single molecule Förster resonance energy transfer (FRET, also known as fluorescence resonance energy transfer) (Chowdhury et al, 2023). As IDPs/IDRs (free and even in most of their complexes) are a lot more dynamic; NMR and FRET constitute two powerful techniques for studying these interactions.…”
Section: Interactions Of Idps/idrs With Other Proteins and Surfaces I...mentioning
confidence: 99%
“…Besides single molecule, FRET can give information about rotational motion in the complexes and their hydrodynamic radii. Combining this technique along with microfluidics and temperature jump relaxation kinetics has made it even more versatile; for example, both high and low concentration ranges of the proteins(s) can be used (Chowdhury et al, 2023). An interesting observation is that one can detect formation of an encounter complex before a stable complex emerges in two systems.…”
Section: Interactions Of Idps/idrs With Other Proteins and Surfaces I...mentioning
confidence: 99%
See 1 more Smart Citation
“…24 Various experimental approaches have been used to study the dynamic structures of IDPs, including nuclear magnetic resonance (NMR) spectroscopy, 25 small angle x-ray scattering (SAXS), 26 and single-molecule fluorescence energy resonance transfer (smFRET). 27 However, each method can only provide information about one side of the "elephant." Consequently, integrative approaches combining experimental and computational analysis are necessary to understand the dynamic conformational ensemble of IDPs.…”
mentioning
confidence: 99%